Pelatihan dan Pengaruhnya terhadap Kinerja Karyawan Hotel - Lisna Bantulu; Asminar Mokodongan; Alifia Satirah Sima (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
The background of this research problem is that the management of Aston Hotel & Villas has not optimally carried out training and performance evaluation of hotel employees so that it affects the performance of hotel employees in serving guests. Therefore, this study aims to determine the influence of the training process in improving employee performance. This research method uses a simple quantitative method presented in the form of numbers and presented in the form of proportions. The final results of this study show that training hours have an effect on employee performance at the Aston Gorontalo Hotel and Villas.